Water, ice, society, and ecosystems in the Hindu Kush Himalaya: an outlook - Wester, P.; Chaudhary, S.; Chettri, N.; Jackson, M.; Maharjan, A.; Nepal, Santosh; Steiner, J. F. (International Centre for Integrated Mountain Development, 2023)
The Water, ice, society, and ecosystems in the Hindu Kush Himalaya (HI-WISE) report draws on recent scientific advances to map for the first time the links between the cryosphere, water, biodiversity, and society in the region, charting the impacts of rapid changes in glaciers and snow on people and nature.